Kerusakan Tanaman Pala Akibat Serangan Hama Penggerek Batang (Batocera hercules) - Aminudin Umasangaji; Johan A Patty; A.A Rumakamar (Faculty of Agriculture, Pattimura University, 2012)
One of the major pests that attack nutmeg plants is Batocera Hercules, which can reduce yield both in quantity and quality. An investigation with an aim to determine the level of Batocea hercules attack on three types of nutmeg trees was conducted in Wakate Subdistrict, Watubela Island, Maluku. The study used a survey method by direct observations in the farmers' nutmeg cultivation areas in District Wakate, Watubela Island. The results showed that the attack level by Batocera hercules the cultivation area of the study was 19.19%, with the number of bore holes 2.08. The major attacks occurred on the nutmeg types of Banda, Onin, and cross, at 23.01%, 30.28% and 4.28% intensities, respectively. The intensity of attacks were affected by nutmeg cultural techniques and climatic factors.